Proses Pengambilan Kebijakan Pemerintah Rusia Dalam Aneksasi Krimea - Ramadhani, Rizkyka Emeralda; Sushanti, Sukma; Widya Nugraha, A.A. Bagus Surya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 1 (2019), 2019)
ABSTRACT Russia and Ukraine are two countries with acomplex link. Since the dissolution of the Soviet Union, Russia has been maintaining its stance and status as a great power within the region by exerting a considerable influence on bordering countries such as Ukraine. Several aspects used to maintain said influence are identity, economy, and military power. The same aspects are also the root of many conflicts between the two countries until it escalated in 2014 with Russia’s annexation of Crimea. This research describes the decision-making process of the Russian government using Graham T. Allison’s model of ‘organizational process’. Identified as its organizational actors, Russia shows a pattern of decision-making process when faced with states around its borders. Russia doesn’t hesitate to use all manners of organizational actors under its control to maintain its interests and influence not only above Ukraine, but also as a great power on a global scale. Keywords: Russia, Ukraine, Annexation of Crimea, decision making process